Sylvia's second act ebook A novel. - Yablon, Hillary (2024)
Her husband’s cheating on her. She hates Boca. Sylvia is mad and she isn’t going to take it anymore. She’s moving back north, to the city of her dreams—with her best friend, Evie, in tow. Think a screwball comedy featuring a sophisticated Thelma and Louise with martinis in hand . . . When sixty-three-year-old Sylvia finds her husband in bed with the floozy of their Boca retirement community, she’s shocked and furious . . . at first. By the time her head stops spinning, Sylvia realizes that actually, this isn’t what she wants anymore anyway. So she enlists her best friend, the glamorous older widow Evie, to join her in setting up a new life in Manhattan. Sylvia’s ex-husband may have lost her life savings, but Sylvia and Evie are scrappy and determined, unopposed to pawning jewelry and roughing it in tiny apartments. And before long, Sylvia signs on to revive her decades-old wedding planning business with a former professional rival. Sylvia has a lot to prove, and beneath it all, she can’t help but wonder: Will she ever be able to get back into the dating game? Sylvia doesn't want to be twenty-five or thirty again. Her age gives her wisdom, experience, and perspective. A career, sex, fun, and a new romance—her entire second act is stretched out in front of her, beckoning to her. It’s her time, and watch out, world, Sylvia is coming!